2016
DOI: 10.6061/clinics/2016(04)09
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine-stimulated growth hormone concentrations (cut-off values) measured by immunochemiluminescent assay (ICMA) in children and adolescents with short stature

Abstract: OBJECTIVES:To establish cut-off values for growth hormone concentrations using clonidine as a secretagogue and an immunochemiluminescent assay as the method of measurement and to analyze the response time as well as the influence of gender, nutritional status and pubertal stage.METHODS:A total of 225 tests were performed in 3 patient groups, categorized as group 1 (normal), group 2 (idiopathic short stature) and group 3 (growth hormone deficiency). Among the 199 disease-free individuals, 138 were prepubertal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
(56 reference statements)
1
15
0
2
Order By: Relevance
“…Puberty does not influence GH responsiveness after GHRH or PD+GHRH . Although CT is one of the most widely used GH stimulation test, it is still unclear whether the GH response is affected by pubertal maturation. Gil‐Ad et al in 1979 demonstrated for the first time in 18 children that clonidine was an effective GH‐stimulating agent in prepubertal and adolescent subjects .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Puberty does not influence GH responsiveness after GHRH or PD+GHRH . Although CT is one of the most widely used GH stimulation test, it is still unclear whether the GH response is affected by pubertal maturation. Gil‐Ad et al in 1979 demonstrated for the first time in 18 children that clonidine was an effective GH‐stimulating agent in prepubertal and adolescent subjects .…”
Section: Discussionmentioning
confidence: 94%
“…Gil‐Ad et al in 1979 demonstrated for the first time in 18 children that clonidine was an effective GH‐stimulating agent in prepubertal and adolescent subjects . A number of studies have confirmed the utility of the CT in the diagnosis of GHD, but most of these studies have been performed in prepubertal children, and none has specifically addressed the effect of puberty on the rate of false positive responses in a large number of subjects. Fraser et al studied 41 children and adolescents and concluded that CT produces less false subnormal responses than ITT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations